Natural climate solutions for the United States - Fargione, Joseph E. (Sci Adv, 2018)
Limiting climate warming to <2°C requires increased mitigation efforts, including land stewardship, whose potential in the United States is poorly understood. We quantified the potential of natural climate solutions (NCS)—21 conservation, restoration, and improved land management interventions on natural and agricultural lands—to increase carbon storage and avoid greenhouse gas emissions in the United States. We found a maximum potential of 1.2 (0.9 to 1.6) Pg CO(2)e year(−1), the equivalent of 21% of current net annual emissions of the United States. At current carbon market prices (USD 10 per Mg CO(2)e), 299 Tg CO(2)e year(−1) could be achieved. NCS would also provide air and water filtration, flood control, soil health, wildlife habitat, and climate resilience benefits.